Emerging roles of mitochondria and autophagy in liver injury during sepsis - Toshihiko Aki; Kana Unuma; Koichi Uemura (Cell Stress, 2017)
Recent research indicates crucial roles of autophagy during sepsis. In animal models of sepsis induced by cecal ligation and puncture (CLP) or the systemic administration of lipopolysaccharides (LPS), autophagy is implicated in the activation and/or damage of various cells/organs, such as immune cells, heart, lung, kidney, and liver. Since sepsis is associated with an increased production of pro- as well as anti-inflammatory cytokines, it has long been considered that hypercytokinemia is a fetal immune response leading to multiple organ failure (MOF) and mortality of humans during sepsis. However, a recent paradigm illuminates the crucial roles of mitochondrial dysfunction as well as the perturbation of autophagy in the pathogenesis of sepsis. In the livers of animal models of sepsis, autophagy is involved in the elimination of damaged mitochondria to prevent the generation of mitochondrial ROS and the initiation of the mitochondrial apoptotic pathway. In addition, many reports now indicate that the role of autophagy is not restricted to the elimination of hazardous malfunctioning mitochondria within the cells; autophagy has been shown to be involved in the regulation of inflammasome activation and the release of cytokines as well as other inflammatory substances. In this review, we summarize recent literature describing the versatile role of autophagy and its possible implications in the pathogenesis of sepsis in the liver.